2019
DOI: 10.1111/php.13189
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Cream Protects Ultraviolet B‐induced Photoaging in Balb/c Mice Skin by Increasing Mitochondrial Markers: Changes Lead to Improvement of Histological Appearance

Abstract: Tranexamic acid (TSA) is widely used as an antiaging treatment for reducing melasma and wrinkles. There are various mechanisms for wrinkle formation, and one of them is due to damage of the mitochondria. Research on mitochondria in the skin is very limited, so we are interested to see the changes that occur after application of TSA cream. We explored the effect of TSA on mitochondrial protein levels (PGC1α, Tom20, COX IV), which had affected to skin histological structure. Thirty male, 6‐week‐old, Balb/C mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Eltania et al reported that treatment with TXA-containing cream increased the expression of mitochondrial markers Tom20 and COX IV in mouse skin. 72 These authors also found a TXAenhanced expression of the transcription factor PGC1a, a positive regulator of mitochondrial biogenesis. Collectively, these data demonstrate that TXA stimulates mitochondrial respiratory activity and biogenesis.…”
Section: Txa and Mitochondriamentioning
confidence: 92%
See 1 more Smart Citation
“…Eltania et al reported that treatment with TXA-containing cream increased the expression of mitochondrial markers Tom20 and COX IV in mouse skin. 72 These authors also found a TXAenhanced expression of the transcription factor PGC1a, a positive regulator of mitochondrial biogenesis. Collectively, these data demonstrate that TXA stimulates mitochondrial respiratory activity and biogenesis.…”
Section: Txa and Mitochondriamentioning
confidence: 92%
“…Using mesenchymal stem cells derived from mitoQC mice in which functional mitochondria and mitochondria in autophagosomes can be distinguished by their fluorescence characteristics, we found that TXA not only increased mitochondrial length but also decreased mitophagy. Eltania et al reported that treatment with TXA‐containing cream increased the expression of mitochondrial markers Tom20 and COX IV in mouse skin 72 . These authors also found a TXA‐enhanced expression of the transcription factor PGC1a, a positive regulator of mitochondrial biogenesis.…”
Section: Txa and Mitochondriamentioning
confidence: 92%
“…The distance between the UV light and the skin was 3 cm. (16) During the experiment each mice were irradiated at different cage. After the irradiation, mice were returned to standard cage to get access for food and drink ad libitum.…”
Section: Uv Irradiation and Re Cream Treatmentmentioning
confidence: 99%
“…7 What's more, TA treatment was found to be effective in increasing mitochondrial marker levels and epidermal thickness and reducing dermal elastosis in mice. 9 TA also exhibited an ameliorated function against photoageing of the skin. 8,10 Also, it was revealed that TA could inhibit angiogenesis and melanogenesis in vitro by targeting VEGF receptors.…”
mentioning
confidence: 91%
“…Furthermore, certain clinical studies have reported the overall improvement of melasma patients treated with TA, associated with the proliferation of fibroblasts 8 and the decrease in vessel numbers in the dermis 7 . What's more, TA treatment was found to be effective in increasing mitochondrial marker levels and epidermal thickness and reducing dermal elastosis in mice 9 . TA also exhibited an ameliorated function against photoageing of the skin 8,10 .…”
Section: Introductionmentioning
confidence: 99%